2007
DOI: 10.1007/s00122-007-0535-z
|View full text |Cite
|
Sign up to set email alerts
|

Consistent detection of QTLs for crown rust resistance in Italian ryegrass (Lolium multiflorum Lam.) across environments and phenotyping methods

Abstract: Crown rust, caused by Puccinia coronata f. sp. lolii, is one of the most important diseases of temperate forage grasses, such as ryegrasses (Lolium spp.), affecting yield and nutritional quality. Therefore, resistance to crown rust is a major goal in ryegrass breeding programmes. In a two-way pseudo-testcross population consisting of 306 Lolium multiflorum individuals, multisite field evaluations as well as alternative methods based on artificial inoculation with natural inoculate in controlled environments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…These plants were complemented with eight parental genotypes of four different perennial ryegrass mapping populations, one parent of the p150/112 intraspecific ILGI reference population [4], and two Italian ryegrass plants which have been used to establish the Xtg-ART population characterized for bacterial wilt and crown rust resistance [57,92]. Genomic DNA was isolated from young leaves following a phenol/chloroform extraction protocol with minor modifications described in Jensen et al [2].…”
Section: Methodsmentioning
confidence: 99%
“…These plants were complemented with eight parental genotypes of four different perennial ryegrass mapping populations, one parent of the p150/112 intraspecific ILGI reference population [4], and two Italian ryegrass plants which have been used to establish the Xtg-ART population characterized for bacterial wilt and crown rust resistance [57,92]. Genomic DNA was isolated from young leaves following a phenol/chloroform extraction protocol with minor modifications described in Jensen et al [2].…”
Section: Methodsmentioning
confidence: 99%
“…Two QTLs for crown rust resistance (LpPc1 and LpPc3) have been detected in LG2 of perennial ryegrass (Dumsday et al 2003, Muylle et al 2005. Moreover, another QTL for crown rust resistance has been detected in LG2 of Italian ryegrass (Studer et al 2007). A cluster of crown rust resistance loci (the Pca cluster) has been located on chromosome B in diploid oat (Yu and Wise 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the strong correlations of crown rust disease scores of a set of Italian ryegrass cultivars among sites of the EUCAR-PIA multisite rust evaluation trial (Boller et al 2003;Schubiger et al 2006). Studer et al (2007) also found crown rust resistance of individual genotypes used for a QTL mapping study to be detected consistently over a number of environments. The Italian ryegrass populations described here varied significantly for crown rust resistance, providing opportunities for selection.…”
Section: Disease Resistance Needs Improvementmentioning
confidence: 92%